Characterization of copper-induced-release of exudates by Citrus sinensis roots and their possible roles in copper-tolerance. (December 2022) - Chen, Huan-Huan; Chen, Xu-Feng; Zheng, Zhi-Chao; Huang, Wei-Lin; Guo, Jiuxin; Yang, Lin-Tong; Chen, Li-Song
Abstract: Copper (Cu) excess is often observed in old Citrus orchards. Little information is available on the characterization of Cu-induced-release of root exudates and their possible roles in plant Cu-tolerance. Using sweet orange [ Citrus sinensis (L.) Osbeck cv. Xuegan] seedlings as materials, we investigated the impacts of 0, 0.5, 25, 150, 350, 550, 1000, 2000 or 5000 μM CuCl2 (pH 4.8) on Cu uptake, root exudates [malate, citrate, total phenolics (TP), total soluble sugars (TSS) and total free amino acids (TFAA)], electrolyte leakage and malondialdehyde, and solution pH under hydroponic conditions; the time-course of root exudates and solution pH in response to Cu; and the impacts of protein synthesis and anion-channel inhibitors, and temperature on Cu-induced-secretion of root exudates and solution pH. About 70% of Cu was accumulated in 0 and 0.5 μM Cu-exposed roots, while over 97% of Cu was accumulated in ≥25 μM Cu-exposed roots. Without Cu, the seedlings could alkalize the solution pH from 4.8 to above 6.0. Cu-stimulated-secretion of root exudates elevated with the increment of Cu concentration from 0 to 1000 μM, then decreased or remained unchanged with the further increment of Cu concentration, while root electrolyte leakage and malondialdehyde (root-induced alkalization) increased (lessened) with the increment of Cu concentration from 0 to 5000 μM. Further analysis indicated that Cu-stimulated-secretion of root exudates was an energy-dependent process and could repressed by inhibitors, and that there was no discernible delay between the onset of exudate release and the addition of Cu. To conclude, both root-induced alkalization and Cu-stimulated-release of root exudates played a key role in sweet orange Cu-tolerance via increasing root Cu accumulation and reducing Cu uptake and phytotoxicity. Graphical abstract: Image 1 Highlights: Most of Cu preferentially accumulated in Cu-exposed C. sinensis roots. Root-induced alkalization of a rhizosphere reduced with the increase of Cu supply. Alkalization and Cu-induced release of root exudates involved in Cu-tolerance. Secretion of root exudates was an energy-dependent process. Cu-induced release of root exudates was affected by inhibitors.